VENTRICULAR SEPTAL DEFECT IN INFANTS AND CHILDREN WITH INCREASED PULMONARY VASCULAR RESISTANCE AND PULMONARY HYPERTENSION - SURGICAL MANAGEMENT: LEAVING AN ATRIAL LEVEL COMMUNICATION - Khan, Inam Ullah; Ahmed, Iftikhar; Mufti, Waqar A.; Rashid, Azhar; Khan, Asif Ali; Ahmed, Syed Afzal; Imran, Muhammad (Journal of Ayub Medical College Abbottabad, 2006)
Objective : To evaluate the surgical and medical efficacy of the patients operated for Ventricular Septal Defect (VSD) with Pulmonary Hypertension and Pulmonary Vascular Resistance (PVR). Infants and children with elevated PVR and Pulmonary Hypertension are associated with significant mortality and morbidity after surgical closure. Circulatory assist devices and sophisticated medicines may not be available to help in the management of infants and children with elevated Pulmonary artery pressure and resistance. We left Patent Foramen Ovale (PFO) or made atrial communication to decrease the morbidity and mortality associated with the closure of large VSD in this risky group. Methods : Sixteen infants and children were operated with median age of 12 months, operated by the same surgeon (IU), from January’ 2004 to December’ 2005 . They were with large VSD of elevated PVR (3.9+0.3) and underwent VSD closure leaving PFO or artificial ASD (5mm). Surgical approach was through right atrium. Post operatively, all the patients were electively ventilated for 36 hours. They were given intravenous dilators (Glyceral Trinitrate + Phentolamine) and oral Sildenafil up to 1mg /Kg, six hourly. Five cases went into acute pulmonary hypertensive crisis postoperatively, and were rescued by Prostacycline Nebulization. Results: Sixteen patients had VSD as the primary lesion that underwent operation. The overall early mortality was 6.25% (1/16). There have been no late deaths. Conclusion: Closure of large VSD with elevated PVR can be performed, leaving PFO or artificial ASD, with acceptable mortality and morbidity.